FORTIFICATION OF CAKE WITH CHICKPEA FLOUR AS A PROTEIN ENHANCER - CHANDRASHREE LENKA*, TRIPTI KUMARI and TRUPTI PRADHAN, (The Journal of Research ANGRAU, 2020)
The study was conducted (2018-19) to develop high protein low calorie cake with chickpea flour alongwith whole wheat flour and other ingredients in different proportions as a protein supplement to combatmalnutrition. Four cakes were prepared including control (whole wheat flour only).Nutritional quality and thesensory evaluation of cake was done in accordance with Nutritive value of Indian foods ICMR, numericalscoring test and nine point hedonic scale for six sensory characteristics respectively. Cake C3 prepared withratio of 4:1 chickpea flour and wheat flour was found to be best one with respect to its nutritive value andsensory characteristics.Significantly high difference at P